If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 18 + -3x + -5x + 8 = 42 Reorder the terms: 18 + 8 + -3x + -5x = 42 Combine like terms: 18 + 8 = 26 26 + -3x + -5x = 42 Combine like terms: -3x + -5x = -8x 26 + -8x = 42 Solving 26 + -8x = 42 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-26' to each side of the equation. 26 + -26 + -8x = 42 + -26 Combine like terms: 26 + -26 = 0 0 + -8x = 42 + -26 -8x = 42 + -26 Combine like terms: 42 + -26 = 16 -8x = 16 Divide each side by '-8'. x = -2 Simplifying x = -2
| 32+21x+x^2=12 | | 4-4(y+1)=6-7y | | 3=x^2/1-x | | 2.9*10^(-11)=(x^2)/(0.1-x) | | 2=-1/2 | | Solved=jm | | -4m+5m^2= | | r+s=-3 | | 3y-10=2y+7 | | y^2dx+x^2dy=0 | | 3+55x=44x+5 | | 3+55x=44 | | (4x-1)x(5x+2)=0 | | 11x-18=6x+6 | | 7x-15=x+4 | | 2x^2+2y=0 | | 3cos+2=0 | | 8x-17+31+9x-69-18x=-39 | | 2x+200=12x-10 | | 12=1/5y-2 | | 10z-9z=-15 | | 2x^2+14x-20=0 | | 2+6x=-23+6 | | 2(x+y)=2x+y | | -3x-2x-4x=1 | | 8x-10=2x+3 | | 15/6x14/40x24/21 | | 2x-4x+8=6 | | 8+5=-3 | | p+5=-7 | | 4.4=10 | | 7-y=19 |